Methanogenic toxicity and continuous anaerobic treatment of wood processing effluents. - Vidal, G.; Diez, M. C. (Journal of Environmental Management, 2005)
Wood processing effluents contain different types of phenolic compounds, from simple monomers to high molecular weight (MW) polyphenolic polymers, that can inhibit wastewater treatment. This work presents a comparative study of the methanogenic toxicity produced by three wood processing effluents (hardboard, fiberboard and BKME (kraft mill effluent)) using Pinus radiata, Eucalyptus and Tepa as feedstock (the last one being a native Chilean tree species). This study evaluates the influence of non-adapted granular and adapted flocculent sludge on forest industrial wastewater treatment as well as continuous anaerobic biodegradation of hardboard processing effluent using the upflow anaerobic sludge blanket (UASB). The adapted biomass (flocculent sludge) did not show any lag-phase signs. The 50% IC (the concentration causing 50% inhibition of methanogenic activity) was 4.3g COD-effluent (chemical oxygen demand (COD)-of the effluent)/l and 2.8g COD-effluent/l for the flocculent sludge and the granular sludge, respectively. The UASB system worked at low organic load rates (0.1-0.4g COD/l d) with the COD removal ranging between 10 and 30%, and color removal did not occur under anaerobic conditions due to high MW. Indeed, the MW analysis indicates the presence of phenolic compounds over 25,000Da in the anaerobic effluent. Copyright (c) 2004 Elsevier Ltd